Two essays on education and governament policies - Maestri, Lucas Jóver (2005)
Whether human capital increases or decreases wage uncertainty is an open ques- tion from an empirical standpoint. Yet, most policy prescriptions regarding human capital formation are based on models that impose riskiness on this type of invest- ment. We slightly deviate from the rest of the literature by allowing for non-linear income taxes in a two period model. This enables us to derive prescriptions that are robust to the risk characteristics of human capital: savings should be discouraged, human capital investments encouraged and both types of investment driven to an e¢ cient level from an aggregate perspective. These prescriptions are also robust to what choices are observed, even though the policy instruments used to implement them are not.